Explorations in pragmatic economics : selected papers of George A. Akerlof (and co-authors). - Akerlof, George A., 1940- (Oxford : Oxford University Press, 2005)
This collection of Akerlof's most important papers provide both an introduction to Akerlof's work and a grounding in modern economics. Divided into two broad areas, micro-and macroeconomics, they cover the economics of information; the theory of unemployment; macroeconomic equilibria; the demand for money; psychology and economics; and the nature of discrimination and other social issues. The collection closes with Akerlof's 2001 Nobel Lecture, in which he argues that it is imperative that macroeconomics be considered inherently behavioural.
Includes bibliographical references
rpm 23/10/13
Loans
Keywords: Economics